Hubungan Penerapan E-Absen terhadap Kinerja Pegawai di RSUD Dr. Soehadi Prijonegoro Sragen - Tafdilla Rahmawati; Muhlizardy Muhlizardy (STIKes Ibnu Sina Ajibarang, 2024)
Employee performance is one of the important things needed by the company, especially hospitals in achieving both short-term and long-term goals. Therefore, improving the performance of hospital employees is one of the most important things to maintain the quality of health services provided to patients. The purpose of this study was to analyze the relationship between the implementation of E-Absenteeism and employee performance at RSUD dr. Soehadi Prijonegoro Sragen. This research method is a type of quantitative research with a descriptive research design that aims to determine the picture of the relationship between the implementation of E-Absenteeism and employee performance at RSUD dr. Soehadi Prijonegoro Sragen. The population of this study were all non-medical employees working at RSUD dr. Soehadi Prijonegoro Sragen with a total of 76 employees. The sample of this study was total sampling that met the inclusion criteria. The data collection technique used the Likert scale. Data analysis used the product moment correlation technique with the Alpha Cronbach test technique. The data collection technique used the Spearman Rank test of 0.002 (P <0.05) with a coefficient value of 0.351. That there is a significant relationship between the implementation of E-Absenteeism and employee performance at RSUD dr. Soehadi Prijonegoro, Sragen.